2016
DOI: 10.1021/acsnano.6b05692
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Optimization of Carbon Radicals on Hydrated Graphene Oxide for Ubiquitous Antibacterial Coatings

Abstract: While the antibacterial properties of graphene oxide (GO) have been demonstrated across a spectrum of bacteria, the critical role of functional groups is unclear. To address this important issue, we utilized reduction and hydration methods to establish a GO library with different oxidation, hydroxyl, and carbon radical (•C) levels that can be used to study the impact on antibacterial activity. Using antibiotic-resistant (AR) bacteria as a test platform, we found that the •C density is most proximately associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
173
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 47 publications
6
173
2
1
Order By: Relevance
“…Due to the fact that 1 O 2 species are highly reactive with an extremely short half-life within tens of nanoseconds, the distance allowing for 1 O 2 diffusion in cytoplasm is limited. [19] However, the highly oxidative nature of 1 O 2 species may cause immediate oxidation of cytoplasmic substances nearby, thus elevating the intracellular ROS level. In this respect, we studied the changes of ROS level of cells treated with IO-LAHP NPs using a 2′,7′-dichlorodihydrofluorescein diacetate probe (H 2 DCFDA).…”
mentioning
confidence: 99%
“…Due to the fact that 1 O 2 species are highly reactive with an extremely short half-life within tens of nanoseconds, the distance allowing for 1 O 2 diffusion in cytoplasm is limited. [19] However, the highly oxidative nature of 1 O 2 species may cause immediate oxidation of cytoplasmic substances nearby, thus elevating the intracellular ROS level. In this respect, we studied the changes of ROS level of cells treated with IO-LAHP NPs using a 2′,7′-dichlorodihydrofluorescein diacetate probe (H 2 DCFDA).…”
mentioning
confidence: 99%
“…The Image-iT Lipid Peroxidation Assay enables the detection of lipid peroxidation in live cells through oxidation of BODIPY 581/591 C11 reagent, which will display a shift in peak fluorescence emission from ~590 nm to ~510 nm. Fluorescence from live cells shifts from red to green, providing a ratiometric indication of lipid peroxidation [19, 61]. These assays provide simple and sensitive approaches and can be adapted easily to high-throughput applications.…”
Section: Fundamental Elements To Establish a Predictive Toxicologimentioning
confidence: 99%
“…85 In addition, they could attach to cell membrane as a 2D planar material and induce membrane damage and cytotoxicity. 86 One possible approach to reduce ECN cytotoxicity is surface functionalization. Wang et al 83 demonstrated that coating multiwall CNTs with a tri-block copolymer (Pluronic F108) mitigates their toxicity by preventing the lysosomal membrane damage and subsequent inflammatory pathways.…”
Section: Carbonaceous Nanomaterialsmentioning
confidence: 99%